1999
DOI: 10.1038/sj.onc.1203152
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of protein tyrosine phosphatases in activation of the trimeric G protein Gq/11

Abstract: A variety of receptors coupled to the heterotrimeric guanine nucleotide-binding protein G q/11 stimulate intracellular Ca 2+ release through inositol (1,4,5)-trisphosphate (IP 3 ) formation. We previously reported that tyrosine phosphorylation of the a subunit of the G q/11 protein by protein tyrosine kinases (PTKs) regulates the activation of G q/11 protein. Here we show that protein tyrosine phosphatases (PTPs) are also essential for G q/11 protein activation. We ®nd that G q/11 protein-coupled receptor-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
(20 reference statements)
1
10
1
Order By: Relevance
“…C1165S to promote tyrosine phosphorylation of G␣ q without leading to its activation conflicts with the model proposed by Umemori et al (13) suggesting that tyrosine phosphorylation occurred downstream of GTP binding. We decided to investigate whether phosphorylation of G␣ q was required for activation of phospholipase C. Cultures of Swiss 3T3 cells were treated with the broad spectrum tyrosine kinase inhibitor genistein to block phosphorylation of G␣ q .…”
Section: Pmt Activation Of G Q Is Not Dependent On G Q Tyrosine Phospcontrasting
confidence: 50%
See 4 more Smart Citations
“…C1165S to promote tyrosine phosphorylation of G␣ q without leading to its activation conflicts with the model proposed by Umemori et al (13) suggesting that tyrosine phosphorylation occurred downstream of GTP binding. We decided to investigate whether phosphorylation of G␣ q was required for activation of phospholipase C. Cultures of Swiss 3T3 cells were treated with the broad spectrum tyrosine kinase inhibitor genistein to block phosphorylation of G␣ q .…”
Section: Pmt Activation Of G Q Is Not Dependent On G Q Tyrosine Phospcontrasting
confidence: 50%
“…Several neuropeptides that regulate cell growth and differentiation induce tyrosine phosphorylation of G␣ q . Recent studies have indicated that G␣ q phosphorylation forms part of a novel cycle in which tyrosine kinases and phosphatases regulate G q activation (11)(12)(13). The aim of the present study was to further investigate the role of phosphorylation using PMT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations